The global syndemic of metabolic diseases in the young adult population: A consortium of trends and projections from the Global Burden of Disease 2000–2019 - Chong, Bryan; Kong, Gwyneth; Shankar, Kannan; Chew, H.S. Jocelyn; Lin, Chaoxing; Goh, Rachel; Chin, Yip Han; Tan, Darren Jun Hao; Chan, Kai En; Lim, Wen Hui; Syn, Nicholas; Chan, Siew Pang; et al. (Metabolism, clinical and experimental, 2023)
A significant proportion of premature deaths globally are related to metabolic diseases in young adults. We examined the global trends and mortality of metabolic diseases in individuals aged below 40 years using data from the Global Burden of Diseases, Injuries and Risk Factors Study (GBD) 2019. From 2000 to 2019, global estimates of deaths and disability-adjusted life years (DALYs) were described for metabolic diseases (type 2 diabetes mellitus [T2DM], hyperlipidemia, hypertension, obesity, non-alcoholic fatty liver disease [NAFLD]). Subgroup analyses were performed based on sex, geographical regions and Socio-Demographic Index (SDI). Age-standardised death and DALYs were presented per 100,000 population with 95 % uncertainty intervals (UI). Projections of mortality and DALYs were estimated using regression models based on the GBD 2019 data and combining them with Institute for Health Metrics and Evaluation projection counts for years up to 2050. In 2019, the highest age-standardised death rates were observed in hypertension (133·88 [121·25–155·73]), followed by obesity (62·59 [39·92–89·13]), hyperlipidemia (56·51 [41·83–73·62]), T2DM (18·49 [17·18–19·66]) and NAFLD (2·09 [1·61–2·60]). Similarly, obesity (1932·54 [1276·61–2639·74]) had the highest age-standardised DALYs, followed by hypertension (2885·57 [2580·75–3201·05]), hyperlipidemia (1207·15 [975·07–1461·11]), T2DM (801·55 [670·58–954·43]) and NAFLD (53·33 [40·73–68·29]). Mortality rates decreased over time in hyperlipidemia (−0·6 %), hypertension (−0·47 %), NAFLD (−0·31 %) and T2DM (−0·20 %), but not in obesity (1·07 % increase). The highest metabolic-related mortality was observed in Eastern Mediterranean and low SDI countries. By 2050, obesity is projected to contribute to the largest number of deaths (102·8 % increase from 2019), followed by hypertension (61·4 % increase), hyperlipidemia (60·8 % increase), T2DM (158·6 % increase) and NAFLD (158·4 % increase), with males continuing to bear the greatest burden across all metabolic diseases. The growing burden of metabolic diseases, increasing obesity-related mortality trends, and the sex-regional-socioeconomic disparities evident in young adulthood, underlie the concerning growing global burden of metabolic diseases now and in future. The ‘Global Metabolic Syndemic’ framework. [Display omitted] •In 2019, the highest age-standardised DALYs were observed in obesity.•The highest age-standardised death rates in 2019 were observed for hypertension.•Eastern Mediterranean and low SDI countries had highest metabolic-related deaths.•Obesity surpasses hypertension as main driver of metabolic-related deaths by 2050.•Males will likely continue to bear the largest burden of metabolic diseases in 2050.